2006
DOI: 10.1248/yakushi.126.643
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Examination and Analysis of Mortality in DBA/2 Mouse Vasculitis Induced with CAWS, a Water-soluble Extracellular Polysaccharide Fraction Obtained from <i>Candida albicans</i>

Abstract: CAWS, a water-soluble extracellular polysaccharide fraction obtained from the culture supernatant of Candida albicans, is one of the fungal pathogen-associated molecular patterns (PAMPs). It has been reported to show potent activity inducing arteritis and coronaritis in mice. Especially, CAWS-induced arteritis has a 100% incidence and severe mortality in the DBA/2 mouse strain. This artiˆcial vasculitis was reported to provide a good murine model of Kawasaki disease and other in‰ammatory vascular disease. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 22 publications
0
23
0
2
Order By: Relevance
“…Our research group applied CAWS to this model and demonstrated that arteritis, similar to that by CADS, was induced, and have begun precisely analyzing CAWS-induced vasculitis (CAWS-vasculitis) 3 . The coronary arteritis induced by CAWS was accompanied by hypertrophy of the tunica intima, the rupture of elastic fibers, diffuse invasion by lymphocytes, histiocytes, fibroblasts, smooth muscle cells, and eosinophils of vascular endothelial cells, and lesions surrounding blood vessels 4 . Based on such characteristics, the coronary arteritis induced by CAWS was presumed to be proliferative granulomatous coronary arteritis, which is different from fibrinoid arteritis.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group applied CAWS to this model and demonstrated that arteritis, similar to that by CADS, was induced, and have begun precisely analyzing CAWS-induced vasculitis (CAWS-vasculitis) 3 . The coronary arteritis induced by CAWS was accompanied by hypertrophy of the tunica intima, the rupture of elastic fibers, diffuse invasion by lymphocytes, histiocytes, fibroblasts, smooth muscle cells, and eosinophils of vascular endothelial cells, and lesions surrounding blood vessels 4 . Based on such characteristics, the coronary arteritis induced by CAWS was presumed to be proliferative granulomatous coronary arteritis, which is different from fibrinoid arteritis.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of serial sections of the aorta stained with H&E suggested that the vasculitis in CBA/N mice was mild compared with that in DBA/2 mice, because aortic stenosis was mild and no reduction in survival rate was observe after CAWS administration (10,14). Previous studies have shown that elastic fiber injury occurs in the aorta close to the beginning of the coronary artery in mice that develop CAWS-vasculitis (10). A similar phenomenon was observed in CBA/N mice as well.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that CAWS-vasculitis begins to develop ϳ1 wk after CAWS administration (10). Using ELISA, serum cytokine production was measured in the late phase after CAWS administration (4 mg/0.2 ml PBS) when the vasculitis was thought to have developed (Fig.…”
Section: Blood Cytokine Production In the Late Phase After Caws Adminmentioning
confidence: 99%
“…In a mouse model, intraperitoneal injection of CAWS produces coronary arteritis in 100% of cases with fatal outcome in one particular strain, the DBA/2 mouse [8], whereas 71% C3H/HeN mice were affected, and none of the CBA/JN mice developed arteritis, suggesting genetic susceptibility [9]. This group has demonstrated linkage between susceptibility to arteritis in mice and loci on chromosome 1 that include inflammatory cytokine receptors such as interluekin-1 receptor (IL-1R) and tumor necrosis factor receptor (TNFR).…”
Section: Discussionmentioning
confidence: 99%